Cell-targeted gene modification by delivery of CRISPR-Cas9 ribonucleoprotein complexes in pseudotyped lentivirus-derived nanoparticles - Ian Helstrup Nielsen; Anne Bruun Rovsing; Jacob Hørlück Janns; Emil Aagaard Thomsen; Albert Ruzo; Andreas Bøggild; Frederikke Nedergaard; Charlotte Thornild Møller; Thomas Boesen; Søren Egedal Degn; Jagesh V. Shah; Jacob Giehm Mikkelsen (Elsevier, 2024)
To fully utilize the potential of CRISPR-Cas9-mediated genome editing, time-restricted and targeted delivery is crucial. By modulating the pseudotype of engineered lentivirus-derived nanoparticles (LVNPs), we demonstrate efficient cell-targeted delivery of Cas9/single guide RNA (sgRNA) ribonucleoprotein (RNP) complexes, supporting gene modification in a defined subset of cells in mixed cell populations. LVNPs pseudotyped with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein resulted in angiotensin-converting enzyme 2 (ACE2)-dependent insertion or deletion (indel) formation in an ACE2+/ACE2− population of cells, whereas Nipah virus glycoprotein pseudotyping resulted in Ephrin-B2/B3-specific gene knockout. Additionally, LVNPs pseudotyped with Edmonston strain measles virus glycoproteins (MV-H/F) delivered Cas9/sgRNA RNPs to CD46+ cells with and without additional expression of SLAM (signaling lymphocytic activation molecule; CD150). However, an engineered SLAM-specific measles virus pseudotype (measles virus-hemagglutinin/fusion [MV-H/F]-SLAM) efficiently targeted LVNPs to SLAM+ cells. Lentiviral vectors (LVs) pseudotyped with MV-H/F-SLAM efficiently transduced >80% of interleukin (IL)-4/IL-21-stimulated primary B cells cultured on CD40 ligand (CD40L)-expressing feeder cells. Notably, LVNPs pseudotyped with MV-H/F and MV-H/F-SLAM reached indel rates of >80% and >60% in stimulated primary B cells, respectively. Collectively, our findings demonstrate the modularity of LVNP-directed delivery of ready-to-function Cas9/sgRNA complexes. Using a panel of different pseudotypes, we provide evidence that LVNPs can be engineered to induce effective indel formation in a subpopulation of cells defined by the expression of surface receptors.